The Influence of Transformational Leadership and Compensation on Organizational Citizenship Behavior (OCB) with Mediation of Work Satisfaction Study at PT Jasa Raharja Branch DKI Jakarta - Zulkarnaen, Sayer; Arijanto, Agus (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study discusses the influence of transformational leadership and compensation on Organizational Citizenship Behavior through the mediating variable work satisfaction at PT Jasa Raharja DKI Jakarta Branch. For this reason, this study aims to find out whether these variables have an influence on Organizational Citizenship Behavior among employees of PT Jasa Raharja DKI Jakarta Branch considering that the company has a high achievement target so that coordination and mutually helpful behavior is needed so that coordination within and between divisions can be better. solid to reduce the selfish interests of the division. This study uses a quantitative approach with data analysis methods using SEM PLS. The total population is 72 employees at PT Jasa Raharja DKI Jakarta Branch using a sampling technique using saturated sampling by the existing permanent employees, namely 72 employees. Study data was collected through distributing questionnaires. According to the study's findings, work satisfaction, remuneration, and transformational leadership all significantly and favorably influence organizational citizenship behavior. Work satisfaction is positively and significantly impacted by transformational leadership as well as compensation factors.